Indian Women Entrepreneurs - Issues and Prospects - Bhatia, Raminder; Kaur, Baljinder (Indian Journal of Finance, 2010)
Entrepreneurship is the propensity of mind to take the risk with confidence to achieve a pre-determined business or industrial objective. Encouraging entrepreneurship symbolizes innovation and a dynamic economy. So it is the function of creating something new, organizing and coordinating it and undertaking risk and handling economic uncertainty with confidence. Entrepreneurs organize the business by using various traits and tactics like leadership, innovation, decision making and managerial caliber so as to run their business profitably.